Depression, Anxiety And Stress Among Medical And Allied Health Sciences Students At Sargodha Medical College - Raza, Muhammad Saeed; Maqbool, Ahsan; Zahid, Sana; Malik, Shoaib Ahmad; Yousaf, Ayesha; Rauf, Kashif (Journal of Rawalpindi Medical College, 2023)
Objective: This study attempts to determine the frequency of depression, anxiety and stress and associated factors among medical and allied health sciences students of Sargodha Medical College. Methods: The nature of the study is cross-sectional, among 350 (175 each) medical and allied health sciences students of Sargodha Medical College. The students were recruited using convenient sampling. Socio-demographic information was recorded and depression, anxiety and stress were assessed using the depression, anxiety and stress scale (DASS-21). Statistical Package for Social Sciences (SPSS) version 24.0 was used for data entry and analysis. Results: The study shows that nearly half of medical students (53.1%) had depression, 69.7% had anxiety and 44% had stress; while among allied health sciences students, 60.6% were depressed, 73.7% had anxiety and 45.1% had reported stress. The mean depression score among medical students was 12.19 ± 9.98 and 13.29 ± 11.12 among allied health sciences students (p≤0.332). Conclusion: Based on the results, it is recommended that various methods should be adapted and prioritized for enhancing the mental health of the students to support and improve academic learning among students. Keywords: Depression, Anxiety, Stress, mental health, medical students, allied health students